PENERAPAN UNDANG-UNDANG TINDAK PIDANA PENCUCIAN UANG DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI DALAM UPAYA MENGOPTIMALKAN PENGEMBALIAN KERUGIAN NEGARA (Studi Putusan Mahkamah Agung Nomor: 1605 K/Pid.Sus/2014) - Budi Bahreisy; Muhammad Hamdan; Mahmud Mulyadi; Jusmadi Sikumbang (Universitas Sumatera Utara, 2015)
ABSTRACT Corruption lately is getting more discussed, either in print, electronic or in seminars, workshops, discussions, and so on. The wealth gained from the crimes of corruption is usually can not directly be used because of the fear nor indicated as money laundering. For it is usually the perpetrators seek to hide the origin of such property by putting them into the banking system (financial system). The issues raised in this thesis is the relationship between corruption and money laundering and how the implementation of the law of money laundering in the eradication of corruption in the Supreme Court ruling No. 1605K / Pid.Sus / 2014. The method used in this thesis is a normative juridical research methods which is descriptive analysis using primary legal materials, secondary, and tertiary that will be analyzed qualitatively. The results showed that the Corruption and money laundering has a very close relationship. It can be clearly viewed in Pasal 2 (1) of UU No. 8 of 2010. Application of the law of money laundering in the eradication of corruption in the Supreme Court's decision No: 1605 K / Pid.Sus / 2014 the District Court apply the UU No. 8 of 2010 to the corruption case, which is 5 years in prison, fines, recompense, and seizing the assets owned by the defendant from criminal act. At the level of the High Court, judges only fix the decision of Medan District Court that the verdict only increase the imprisonment of the accused for 6 (six) years in prison and on appeal judges only replace imprisonment to 6 (six) months if the fines is not paid by the defendant and replace imprisonment for two (2) years if the defendant can not pay the compensation. From the analysis of the case against the Supreme Court's decision No: 1605 K / Pid.Sus / 2014 in consideration from the judge, element can be harm state finance and economies which is based on results of calculations performed by BPKP North Sumatra province, it can be argued Judge Corruption Court in Medan not guided by UU No. 17 of 2003 regarding State Finance,UU No. 1 of 2004 concerning the state treasury, and the UU No. 15 of 2004 on Management and State Financial Responsibility very clearly gives the BPK in determining financial loss countries / regions. Keyword : Money Laundering, Corruption, State Financial